Morfologia do tubo digestório e diversidade de endoparasitos intestinais em Rhytiodus microlepis (Characiformes: Anostomidae): sazonalidade na relação parasito-hospedeiro em um lago de várzea da Amazônia Central - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
This study aimed to evaluate the intestinal endoparasite fauna in Rhytiodus microlepis and its relationship with bioecological factors. In the first chapter the anatomical, histological and histochemical characteristics of the R. microlepis digestive tract were described in order to provide the basis for the analyzes of the second chapter. In general the digestive tract of the species is similar to that of other teleost fishes and consists of esophagus, stomach and intestine. However, peculiarities were observed, such as the muscular layer of the intestine, which is organized into three muscular tunics: internal longitudinal muscle, internal circular muscle and external longitudinal muscle, a configuration that has never been previously reported for teleost fishes. Histochemical analysis revealed that the esophagus, the pyloric region of the stomach and the intestine reacted positively to all histochemical methods employed, except for the cardic and fundic regions of the stomach, which reacted positively only to PAS and PAS + AB 2.5. The second chapter aimed to study the R. microlepis endoparasite fauna during flood and dry seasons in the region of lake Catalão, Iranduba, Amazonas, Brazil, correlating infection levels with distribution, endoparasite density, and degree of pathogenicity. Of the individuals analyzed, 100% were parasitized by Digenea metacercariae and 94.7% by the acanthocephalan Octospiniferoides incognita. Both endoparasites taxa occurred during flood and dry season; however, Digenea metacercaria intensity and abundance was significantly higher during the dry season. Regarding the distribution of parasites, both species occurred along the tube, with the Digenea metacercariae having a clear preference for the earliest portions and the acantocephalan O. incognita for the intermediate portions of the intestine. Metacercariae were recorded at high frequency in the mucosal layer (lamina propria region), while the acanthocephalan were more frequent in the lumen. The histopathological alteration index values for the organ were significantly higher in drought than in flood. Considering the aspects evaluated in this study, histology was an effective tool to know the morphological characteristics of the R. microlepis digestive tract with applicability to infer the distribution patterns of intestinal endoparasites found, the host responses to these infestations and also as both respond to swings that occur at the water level of Catalão lake.
Keywords: Peixes - Aparelho digestivo; Peixes - Parasitos; Histopatologia; CIÊNCIAS BIOLÓGICAS: ZOOLOGIA; Morfohistoquímica; Tubo digestório; Endohelmintos; Histopatologia semiquantitativa; Sazonalidade